Dystopic Marital Narratives at the Opéra-Comique during the Regency - Ray, Marcie (Música em Perspectiva, 2013)
In the early eighteenth century, most comedies that featured lovers conclude in marriage or the promise of marriage. Comedies adapted from the commedia dell’arte tradition, a widely known comic genre, rigorously applied the conventional comic formula even if lovers have to be shuffled around at the denouement to ensure that each character ended up with a mate. However, in the early decades of the eighteenth century, two comedies premiering at the Opéra-Comique in Paris experimented with this traditional formula, and critiqued the happiness promised by such an ending. The first was Louis Fuselier, Jacques-Philippe D’Orneval, and Alain-René Le Sage’s Le Tableau de mariage (The Tableau of Marriage, 1716), which explored the theme of domestic abuse, while the second, D’Orneval and Le Sage’s L’Isle des Amazones (The Island of the Amazons, 1718), featured an Amazonian utopia where women married only once and for only three months. These opéras-comiques, like dystopic fairy tales before them, critique marriage, and experiment with the conventional ending because it no longer seemed to offer, without irony, the promise of lasting happiness.